PSO-Tuned PID Controller for a Nonlinear Gantry Crane System - Jaafar, Hazriq Izzuan (2012)

(untitled)
This paper presents development of an optimal PID controller for control of a nonlinear gantry crane system. An improved PSO algorithm based on a priority-based fitness approach is implemented for finding optimal PID parameters. The system dynamic model is derived using Lagrange equation. A combination of PID and PD controllers are utilized for position and oscillation control of the system. System responses including trolley displacement and payload oscillation are observed and analyzed. Simulation is conducted within Matlab environment to verify the performance of the controller. It is demonstrated that the controller is effective to move the trolley as fast as possible to the desired position with low payload oscillation technique.